Поліпшений захист мікроконтролера від читання - Воргуль, О. В.; Білоцерківець, О. Г. (My University, 2021)
Embedded system designers need to regularly store confidential information, such as cryptographic keys, user data, proprietary algorithms, and other forms of intellectual property in the firmware of microcontrollers. To prevent the retrieval of confidential information stored in microcontrollers (MCUs), many MCUs implement functionality known as read protection. This limits the reading of the internal memory through debugging or software interfaces. But these methods of protection are not always reliable
Keywords: мікроконтролер; захист читання; функція PALL